Cardiovascular and respiratory evaluation during cervical myelography using ioversol in dogs - Araujo Melo e Silva, Sergio Ricardo; Tudury, Eduardo Alberto; Albuquerque, Veronica Batista [UNESP]; Araujo, Felipe Purcell de [UNESP]; Breda Souza, Talita Floering [UNESP]; Nobrega Neto, Pedro Isidro da; Bonelli, Marilia de Albuquerque (Univ Federal Rural Pernambuco, 2011)
The objective of this study was to evaluate cardiovascular and respiratory effects associated with neck flexion, subarachnoid puncture, cerebrospinal fluid drainage and the subarachnoid infusion of ioversol (320mgl/mL) in dogs under isoflurane general anesthesia. The dogs received infusion of: autologous cerebrospinal fluid at 38 degrees C (GC - control group); ioversol 0.3mL/ Kg at 25 degrees C (GI25) and heated to 38 degrees C (GI38). Heart rate, systolic and diastolic arterial pressure, respiratory rate, oxyhemoglobin saturation and electrocardiography readings were recorded. The results showed that cervical myelography with ioversol 320mgl/mL at 0.3mL/Kg (25 C-degrees and 38C degrees) did not significantly alter recorded parameters, except for an elevation in arterial pressure.
Keywords: Myelography; optiray 320; cardiac arrhythmia; arterial pressure; dogs